2012
DOI: 10.3846/1648715x.2011.602756
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Residential Property Price Index and Macroeconomic Indicators in Dubai Housing Market / Santykis Tarp Gyvenamojo Nt Indekso Ir Makroekonominių Rodiklių Dubajaus Būsto Rinkoje

Abstract: The main purpose of this study is to investigate whether there is a long-run relationship between macroeconomic indicators and property price index in Dubai. This paper uses the monthly data for the eight year period from January 2003 to December 2010. In order to identify long term equilibrium between property price index and macroeconomic indicators, cointegration analyses are utilized for the study. The results of the empirical analyses show that there is a long term positive equilibrium relationship not on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…In modelling such relationships, several models are developed adopting an economic and finance framework known as Vector Autoregressive (VAR) approach together with Granger Causality test. This framework is widely used and accepted by international researchers to identify relationship between variables in the real estate markets (Brooks 2008;Koop 2008;Gupta et al 2012;Hepsen, Vatansever 2012;Holstein et al 2013). We will therefore use the same framework to evaluate the relationship between the housing market and housing finance system in Malaysia.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In modelling such relationships, several models are developed adopting an economic and finance framework known as Vector Autoregressive (VAR) approach together with Granger Causality test. This framework is widely used and accepted by international researchers to identify relationship between variables in the real estate markets (Brooks 2008;Koop 2008;Gupta et al 2012;Hepsen, Vatansever 2012;Holstein et al 2013). We will therefore use the same framework to evaluate the relationship between the housing market and housing finance system in Malaysia.…”
Section: Methodsmentioning
confidence: 99%
“…The outcome of their analysis shows that variables in housing market fall in response to the tightening of monetary policy. Furthermore, a study by Hepsen and Vatansever (2012) was conducted to identify the relationship between the house price index and macroeconomic variables in Dubai. Hepsen and Vatansever (2012) found that there is a long term positive equilibrium relationship between the Dubai Property Price Index (DRPPI) and gold price as well as with the total volume of total direct foreign trade.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The span of our data coverage is justified by the fact that many studies examined similar period. Among the studies are Ibrahim and Law (2014) for Malaysia using quarterly data from 1999Q1 to 2011Q4, Hepsen and Vatansever (2012) for Dubai market employing monthly data from 2003 to 2010, Mallick and Mahalik (2012) for the case of China using quarterly data from 1999 to 2009, and Liang and Chao (2007) for China using quarterly data spanning from 1999 to 2006. Therefore, based on prior studies we believe that the 14 years period is justifiable to capture the long term relationship while cautioning the readers about the data limitation.…”
Section: Empirical Literaturementioning
confidence: 99%
“…In Europe, the value of properties ranges from 0.4 times the GDP in Poland to 1.78 times in France, as reported by Colleta (2013). On the other hand, there is a strong correlation between the housing market, in particular the real estate prices index, and macroeconomics (Hepsen and Vatansever 2012). Goodhart and Hofmann (2008) highlight the interdependence between housing cost dynamics and economic activity, bank credit, inflation, and the implications of house price fluctuations for monetary and public policies.…”
Section: Introductionmentioning
confidence: 99%